A saúde mental masculina: uma análise da política pública nacional de atenção integral à saúde do homem - (:unkn) unknown (Universidade Federal do Pampa, 2022)
This final paper aims to address the insertion of male mental health in PNAISH - the National Comprehensive Healthcare Policy for Men. A base understanding for this paper is that the effectiveness of this public policy contributes to the development of a fair and democratic society. It is necessary to rethink men's health as something that also includes the psychological life within the right to health. It is known that in order to have access to mental health as a promotion of the right to health, it is necessary to invest in the training that gives public service workers and health professionals the subsidies to work on the subject in the clinical context. First of all, PNAISH was presented, in order to know the context of this public policy. Then, there is the discussion on the relationship between men's health and the patriarchal masculinity model, as well as a critical reflection on male mental health. To increase the mental health in PNAISH, communication campaigns, professional training courses, and actions to be implemented by public managers were prescribed. In this context, it is realized the importance of training public service workers and health professionals within the SUS system and of the offering of qualification by the State so that PNAISH can become effective in a concrete way in the context of men's mental health.
Keywords: Saúde mental; Homens; Política pública; Serviços de saúde mental; Homens - Saúde e higiene; Direito à saúde; Identidade de gênero; Mental health; Men; Política Nacional de Atenção Integral da Saúde do Homem; CNPQ::CIENCIAS HUMANAS